Senegal : First Review Under the Policy Coordination Instrument and Request for Modification of Quantitative Targets-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2020)
The Covid-19 pandemic has ended a period of buoyant growth averaging about 6 1\2 percent over the last 6 years. Containment measures, lower external demand, reduced remittances, and the sudden stop of travel and tourism are taking a significant toll on the economy. Without forceful policy measures, the current crisis could unravel development gains over the last decade. The authorities have taken strong actions to contain the pandemic and mitigate its economic fallout, supported by significant additional external financing from Senegal's development partners. The IMF disbursed USD 442 million (100 percent of quota) under the RFI/RCF in April.